Pastoralists' progress: the future for the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Profound and often painful social and economic changes are affecting the lives of the pastoralists of the Sahelian countries. Drought is driving them southwards where they meet with opposition from local farmers. Because of drought the traditional...